Remarkable magnetostructural coupling around the magnetic transition in CeCo0.85Fe0.15Si - Correa, Víctor Félix (2016)
We report a detailed study of the magnetic properties of CeCo0.85Fe0.15Si under high magnetic fields (up to 16 Tesla) measuring different physical properties such as specific heat, magnetization, electrical resistivity, thermal expansion and magnetostriction. CeCo0.85Fe0.15Si becomes antiferromagnetic at TN ≈ K. However, a broad tail (onset at TX ≈ K) in the specific heat precedes that second order transition. This tail is also observed in the temperature derivative of the resistivity. However, it is particularly noticeable in the thermal expansion coefficient where it takes the form of a large bump centered at T X. A high magnetic field practically washes out that tail in the resistivity. But surprisingly, the bump in the thermal expansion coefficient becomes a well pronounced peak fully split from the magnetic transition at T N. Concurrently, the magnetoresistance also switches from negative to positive above TN. The magnetostriction is considerable and irreversible at low temperature (Δ/L (16T) ∼ × 10-4 at 2 K) when the magnetic interactions dominate. A broad jump in the field dependence of the magnetostriction observed at low T may be the signature of a weak ongoing metamagnetic transition. Taking altogether the results indicate the importance of the lattice effects on the development of the magnetic order in these alloys.